2019
DOI: 10.1039/c9qo00092e
|View full text |Cite
|
Sign up to set email alerts
|

Cross coupling of alkylsilicates with acyl chlorides via photoredox/nickel dual catalysis: a new synthesis method for ketones

Abstract: Photoredox/nickel dual catalysis using silicates and acyl chlorides allows a new method of formation of ketones. Flow chemistry can be applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 62 publications
1
26
0
Order By: Relevance
“…Alkyltrifluoroborates, 4m , 5 alkylsilicates, 4l , 6 carboxylic acids, 4n , 7 alkyl oxalates, 8 4-alkyl-1,4-dihydropyridines (DHPs), 4e , 9 and THF 10 have been demonstrated as readily available carbon radical precursors in photochemistry. Using photoredox and nickel dual-catalyzed cascade reactions as a platform, a series of protocols for the difunctionalization of alkynes and alkenes have been established using these radical precursors.…”
Section: C-radicals Involved Photoredox and Nickel Dual-catalyzed Casmentioning
confidence: 99%
“…Alkyltrifluoroborates, 4m , 5 alkylsilicates, 4l , 6 carboxylic acids, 4n , 7 alkyl oxalates, 8 4-alkyl-1,4-dihydropyridines (DHPs), 4e , 9 and THF 10 have been demonstrated as readily available carbon radical precursors in photochemistry. Using photoredox and nickel dual-catalyzed cascade reactions as a platform, a series of protocols for the difunctionalization of alkynes and alkenes have been established using these radical precursors.…”
Section: C-radicals Involved Photoredox and Nickel Dual-catalyzed Casmentioning
confidence: 99%
“…Among them, a class of relatively low oxidation potential of alkyl (bis)catecholatosilicates have recently proven to be efficient radical precursors, as shown by some of us and Molander as well as other groups . They are interesting for their ease of synthesis from the corresponding alkoxysilane or trichlorosilane and for their ability to generate unstabilized primary alkyl radicals, under photoredox‐catalyzed conditions, whether in the presence of classical Ru(II) or Ir(III) photocatalysts or even with an organic dye . The nucleophilic radicals thus formed can be readily engaged in C−C bond formation by addition to various species such as activated alkenes, allylsulfones, imines or recently heteroarenes and N‐acylhydrazone or by nickel catalyzed cross coupling reactions …”
Section: Introductionmentioning
confidence: 99%
“…Especially dicatecholato‐silicate(IV) complexes are frequently used as precursors for either silane synthesis or functionalization of various organic molecules . Most recently, a collaborative research of Ollivier and co‐workers together with Fensterbank and co‐workers demonstrated a new synthesis for ketones, in this context employing acyl chlorides …”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37][38][39][40][41][42][43] Most recently,acollaborative research of Ollivier and co-workerst ogether with Fensterbank and co-workers demonstrated an ew synthesis for ketones,i nt his context employinga cyl chlorides. [44]…”
Section: Introductionmentioning
confidence: 99%